ANALYSIS OF FACTORS INFLUENCING THE PERFORMANCE OF CADETS TRAINED TO OPERATE LOGGING MACHINERY - Petukhov, Igor; Steshina, Lyudmila; Kurasov, Pavel; Andrianov, Yuri (Journal of Applied Engineering Science, 2023)
The paper analyzes factors that affect human productivity when operating logging machinery. It assesses how training machines and simulators influence the results of training. The paper further describes novel methods for testing the psychophysiological traits of human beings that enable evaluating the precision of guiding the implement of the logging machine in horizontal plane as well as by boom extension. The results of testing a group of cadets are presented herein. The research team found the boundaries of the test results obtained by the author-developed methods as compared against the results of final examinations held to complete the logging machinery operation training. The paper will be of interest for human- machine interaction and logging machine training specialists.